How do Earmarked Funds Change the Geographical Allocation of Multilateral Assistance? - Laurent Wagner (Fondation pour les études et recherches sur le développement international (FERDI), 2016)
Almost nonexistent in the early 90s, bilateral development assistance disbursed through earmarked funds co-managed by multilateral donors is playing an increasing role in the aid landscape. While the importance and popularity of these new instruments among traditional donors have increased, their management, their objectives and their implementation remain largely under-documented. Furthermore, the question of the geographical allocation of earmarked funds is becoming more and more important for many stakeholders. We look at the geographic allocation of earmarked multilateral ODA with regard to "performance", the traditional criterion for aid allocation in most Multilateral Development Banks. Our results show that the multiplication of trust funds tend to undermine the role of performance as a core allocation criterion. We also present evidence that recipient executed trust funds at the World Bank over the period 2009-2013 have favored low income and fragile countries despite their low performance. For some countries the share of total aid received from the World Bank beyond the performance based allocation (PBA) is far from negligible.
Keywords: 330; earmarked funds; multilateral assistance; geographical allocation